Optimal Control Strategies for Dengue and Malaria Co-Infection Disease Model - Muhammad Imran; Brett Allen McKinney; Azhar Iqbal Kashif Butt; Pasquale Palumbo; Saira Batool; Hassan Aftab (Mathematics)
Dengue and malaria fever infections are mosquito-borne diseases that pose significant threats to human health. There is an urgent need for effective strategies to prevent, control, and raise awareness about the public health risks of dengue and malaria. In this manuscript, we analyze a mathematical model that addresses the dynamics of dengue–malaria co-infection and propose optimal control strategies across four different scenarios to limit the spread of the disease. The results indicate that non-pharmaceutical interventions are the most effective and feasible standalone strategy, yielding significant reductions in disease transmission. Additionally, vector population control through spraying is identified as the second most significant method, with a proportional decrease in disease prevalence corresponding to the reduction in the mosquito population. While pharmaceutical treatments alone do not fully eradicate the disease, they do contribute to its containment. Notably, the combination of vector control and non-pharmaceutical strategies proved to be the most effective approach, ensuring rapid disease eradication. These findings emphasize the importance of integrated interventions in managing co-infection dynamics and highlight the vital role of prevention-oriented strategies.